Perancangan Media Pembelajaran BimbinganTIK Berbasis Android Siswa SMK Jurusan Bisnis Konstruksi dan Propeti - Indra Wijaya; Lika Jafnihirda; Nur Fadillah (Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to create an Android-based learning media that meets valid, practical and effective requirements for ICT guidance subjects. This research is a Research and Development research conducted at SMK. The test subjects in this study were students of class X BKP at SMK Negeri 1 Padang. The result of the assessment of the three validators as a whole is 91.17% so that the level of validity can be interpreted is very valid to use. The overall practicality assessment is 90.65%, so that the practicality level can be interpreted to be very practical to use, as well as the effectiveness rating of 93.21%, so that the level of effectiveness can beinterpreted very well to use